2017
DOI: 10.3389/fnagi.2017.00376
|View full text |Cite
|
Sign up to set email alerts
|

Economic Cognitions Among Older Adults: Parental Socialization Predicts Financial Planning for Retirement

Abstract: Drawing on the model on financial planning for retirement (FPR), the aim of this work is to explore how parental economic socialization both directly and indirectly affects FPR through the mediation of financial literacy, financial planning decisions and financial management. Data from a sample of 280 participants aged between 45 and 63 years were used. The results show that parental economic socialization directly and indirectly influences FPR. Moreover, parental economic behavior acts as a positive model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 57 publications
4
22
0
3
Order By: Relevance
“…Although an individual's perception of push and pull factors occurs in context, and although an individual's perception of context can lead to the same event being rated as either a push or a pull by different workers (Shultz et al, 1998 ), it seems that a pattern of relationships exists, as Feldman ( 2013 ) suggested. This finding supports the evidence about the impact of positive job characteristics on intended retirement time (Ecklund, 2014 ), as well as the fact that, although people cannot control the external circumstances affecting the retirement process, they can at least anticipate the conditions of the process by retirement planning and preparation programs (Palaci et al, 2017 ).…”
Section: Discussionsupporting
confidence: 82%
“…Although an individual's perception of push and pull factors occurs in context, and although an individual's perception of context can lead to the same event being rated as either a push or a pull by different workers (Shultz et al, 1998 ), it seems that a pattern of relationships exists, as Feldman ( 2013 ) suggested. This finding supports the evidence about the impact of positive job characteristics on intended retirement time (Ecklund, 2014 ), as well as the fact that, although people cannot control the external circumstances affecting the retirement process, they can at least anticipate the conditions of the process by retirement planning and preparation programs (Palaci et al, 2017 ).…”
Section: Discussionsupporting
confidence: 82%
“…For a few of the participants, having a parent who was not adequately financially prepared for retirement encouraged them to think about pension saving. This finding goes some way to answering the question raised by Palaci et al (2017) regarding the extent of negative socialization on economic decisions. Palaci et al also questioned whether a father's influence on his children is greater than a mother's.…”
Section: Discussionmentioning
confidence: 68%
“…Another study, by Gutierrez and Hershey (2014), pointed to parental influences on expected quality of life in retirement but did not determine whether the motives and satisfaction remained as individuals age (the direct impact of parental influence on the middle-aged group in the same study was not observed). By contrast, a more recent quantitative study on economic cognitions found that earlier parental socialization predicted financial planning for retirement amongst older adults (Palaci et al 2017). Other researchers have also noted the impact of parental influence on financial behavior over the longer term (Tang 2017).…”
Section: Intergenerational Similarities In Retirement Savings Behaviormentioning
confidence: 87%
See 1 more Smart Citation
“…Another topical work by F. Palaci, I. Jiménez, G. Topa -"Economic Cognitions Among Older Adults: Parental Socialization Predicts Financial Planning for Retirement" [14] is dedicated to an indirect influence of economic socialization and bases on a financial planning model for one's retirement (FPR). This work regards how parents' economic socialization directly or indirectly has a bearing on the FPR through the mediation in financial awareness, financial planning decisions and financial management.…”
Section: Introductionmentioning
confidence: 99%